Inhibitory Effect of Aqueous Salvia officinalis’s leaves in the Growth of Candida albicans from Infected Women with Vaginal Candidiasis - jasim, Rusul Mohammad; Abd AL-khaliq, Israa Mohammad (AL-Kindy College Medical Journal, 2011)
Background: Salvia officinalis is a plant belong to Labiatae family .The common name of Salvia is sage which mean save. The leaves of Salvia have special oil which is effective against filamentous fungi and yeasts such as Candida albicans which is the causative agent of vaginal candidiasis in women Methods. Cultures from 50 swabs of Candida albicans isolated from vagina of 70 patient women who complains from vaginal problems, their ages (24-43) years from Central City Hospital during Febreoury 2009 to April 2009 were cultured on Sabouraud Dextrose Agar (SDA) .Nystatin was used as positive reference standard to determine the sensitivity of this fungus . and less this concentration there was no minimum inhibition for the Candida Results: The aqueous extract of Salvia officinalis at various concentrations inhibited the growth of C. Albicans . This inhibitions reached to a maximum of 100% for extract at 25 mg / ml and the minimum inhibition was 170 mm at 15 mg /ml for the extract . While the minimum and maximum inhibition for nystatin was at 50 μg/ml,and less concentration. There was no minimum inhibition for the Candida Conclutions : The findings provide support for the use of this plant in traditional medicine for fungal infections especially against candidiasis .